Stiff-man syndrome associated with nocturnal myoclonus and epilepsy. Issue 5 (May 1978) - Martinelli, P; Pazzaglia, P; Montagna, P; Coccagna, G; Rizzuto, N; Simonati, S; Lugaresi, E
Abstract : A case of stiff-man syndrome associated with primary generalised epilepsy is reported. In addition, nocturnal polygraphic recording revealed a nocturnal myoclonus. Detailed examination of the central nervous system did not show specific changes. There is no direct proof as to a spinal or supraspinal origin of the stiff-man syndrome. The absence of specific anatomical lesions may indicate a functional rather than a structural disturbance in its physiopathogenesis.